A comparative review of the efficacy of 24-hour versus 48-hour dose regimen of amoxicillin/ clavulanic acid prophylaxis for postoperative infections following elective caesarean section at the University College Hospital, Ibadan, Nigeria. (2022)
Objectives: To compare the efficacy of 24 hour versus 48 hour prophylaxis of amoxicillin/clavulanic acid in the prevention of postoperative infections. Study Design: This study was a randomized controlled clinical trial conducted in a tertiary hospital in Ibadan, Nigeria. Two hundred and fifty - two pregnant women scheduled for elective caesarean section were randomly assigned into two groups. After the initial pre-incision antibiotic a dmi n i s t r a t i o n , g r o u p A r e c e i v e d t h e Amoxicillin/Clavulanic Acid for 24 hours while group B received the same drug for 48hours. Main Outcomes: Participants were examined on the3rd, 10th and 17th post-operative days for evidence of infections. All entry and analysis of data was by computer using the Statistical Package for Social Sciences version 22 (IBM, New York).Statistically significant differences were determined at p value of< 0.05. Results: The incidence of postoperative wound infection, postoperative fever and endometritis in this study was 5.2%, 9.1% and 5.6% respectively. There were no significant differences in the incidence of postoperative wound infection, postoperative fever and endometritis between the two regimens of antibiotics.